2008
DOI: 10.1074/jbc.m708647200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Differences of the Catalytic and Non-catalytic Domains in Human ADAMTS-4 and ADAMTS-5 in Aggrecanolytic Activity

Abstract: ADAMTS-4 (aggrecanase-1) and ADAMTS-5 (aggrecanase-2) are multidomain metalloproteinases belonging to the ADAMTS family. We have previously reported that human ADAMTS-5 has much higher aggrecanolytic activity than human ADAMTS-4. To investigate the different proteolytic activity of the two enzymes, we generated a series of chimeras by exchanging various non-catalytic domains of the two proteinases. We found that the catalytic domain of ADAMTS-5 has higher intrinsic catalytic ability than that of ADAMTS-4. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
109
1
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 36 publications
6
109
1
5
Order By: Relevance
“…This would indicate that the short aminoterminal extremity of the metalloproteinase domain and/or the 132 amino acid-long spacer domain, which are common in all these constructs, are possibly involved. The spacer domain of ADAMTS-4 or ADAMTS-5 has been shown to modulate the proteolytic activity of the enzyme [48] but a structural function unrelated to the enzymatic activity has never been described so far. As an alternative hypothesis, antiangiogenic activity could be operated by two different TSR1 domains: the first, which is the only one present in the ADAMTS-2 lacking the C-terminal domain, and any of the three TSR1 that are still conserved in the ADAMTS-2 deprived of its central domain.…”
Section: Discussionmentioning
confidence: 99%
“…This would indicate that the short aminoterminal extremity of the metalloproteinase domain and/or the 132 amino acid-long spacer domain, which are common in all these constructs, are possibly involved. The spacer domain of ADAMTS-4 or ADAMTS-5 has been shown to modulate the proteolytic activity of the enzyme [48] but a structural function unrelated to the enzymatic activity has never been described so far. As an alternative hypothesis, antiangiogenic activity could be operated by two different TSR1 domains: the first, which is the only one present in the ADAMTS-2 lacking the C-terminal domain, and any of the three TSR1 that are still conserved in the ADAMTS-2 deprived of its central domain.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies of ADAMTS5/ADAMTS4 chimeric proteases showed that MD5/TCS4 cleaved both IGD and CS-2 sites normally (10). Thus, when combined with MD5, TCS4 can functionally replace TCS5 for both IGD and CS2 cleavage, whereas MD5/TCS13 only preserves IGD cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…The altered properties of chimeric proteases constructed from ADAMTS4 and ADAMTS5 support this concept (10). We have now created chimeric ADAMTS5 and ADAMTS13 proteases and have characterized their activity toward model aggrecan IGD and VWF substrates.…”
mentioning
confidence: 88%
See 2 more Smart Citations